2019
DOI: 10.1002/cbdv.201900062
|View full text |Cite
|
Sign up to set email alerts
|

New Immunomodulating Polyhydroxypregnane Glycosides from the Roots of Cynanchum otophyllum C.K.Schneid.

Abstract: Seven new polyhydroxypregnane glycosides, named cynotophyllosides P–V, together with three known analogs were isolated from the roots of Cynanchum otophyllum C.K.Schneid. Their structures were elucidated by a variety of spectroscopic techniques, as well as acid‐catalyzed hydrolysis. All isolates were tested for their immunological activities in vitro against Con A‐ and LPS‐induced proliferation of mice splenocytes. Immunoenhancing (for 1, 9) and immunosuppressive (for 2) activities were observed. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…1991 ; Zhan et al. 2019 ). This species is one of the most important Chinese traditional herb also called Qingyangshen, it had been widely used in Chinese nationalities of Bai, Naxi and Yi to treat epilepsy and anti-hepatitis for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…1991 ; Zhan et al. 2019 ). This species is one of the most important Chinese traditional herb also called Qingyangshen, it had been widely used in Chinese nationalities of Bai, Naxi and Yi to treat epilepsy and anti-hepatitis for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…[1] There are 53 species and 12 varieties in China, mainly distributed in the northwest and southwest regions. [2] Many plants of this genus are used to treat common and chronic diseases as herbal medicines by local people in China. [3,4,5] Recent phytochemical studies on plants of Cynanchum genus have found many secondary metabolites with antioxidant, [6] antibacterial, [7] antioxidant, [8] and anti-inflammatory [9] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Cynanchum L. is a large genus of the family Asclepiadaceae, comprising more than 200 species and distributed worldwide, especially in east Africa, Mediterranean region, as well as the tropical, subtropical and temperate areas of Europe and Asia [1] . There are 53 species and 12 varieties in China, mainly distributed in the northwest and southwest regions [2] . Many plants of this genus are used to treat common and chronic diseases as herbal medicines by local people in China [3,4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…The polyoxypregnanes and their derivatives as valuable therapeutic agents are naturally occurring C 21 steroidal skeleton or substituted by oligosaccharide chain, benzoyl, acylated tigloyl ester groups, as well as an extra epoxide ring ( Bai et al, 2007 ; Zheng et al, 2014 ), which exhibited diverse biological and medicinal activities, such as anti-inflammatory effect, immune-suppressive effect; chondro-protective effect; and antifungal, antioxidant, antifertility, anti-AchE, and anti-HIV activities ( Abe et al, 2000 ; Niranjan et al, 2002 ; Plaza et al, 2004 ; Deng et al, 2005 ; Li et al, 2007 ; Sanyacharernkul et al, 2009 ; Ni and Ye, 2010 ; Wang et al, 2010 ; Itthiarbha et al, 2012 ; Pang et al, 2015 ; Zhang et al, 2015 ; Gu and Hao, 2016 ; Wang et al, 2016 ; Pang et al, 2017 ; Zhan et al, 2019 ). In particular, many of them have shown prominent anticarcinogenic or cancer inhibitory activities with great research and development potential, and received widespread attention by pharmacologists ( Plaza et al, 2005 ; Panda et al, 2006 ; Bai et al, 2009 ; Shen and Zhang, 2010 ; Zhang et al, 2010 ; Xue et al, 2012 ; Sun et al, 2014 ; Yao et al, 2014 ; Zhang et al, 2015 ; Liu et al, 2018 ; Song et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%